Impedance sensor probe for degradation assessment of cooking oil - Khaled, Alfadhl Yahya; Abd Aziz, Samsuzana; Rokhani, Fakhrul Zaman (The European Society of Agricultural Engineers (EurAgEng), 2014)
Repeated use of cooking oil had been proven hazardous due to degradation process that contributes to the formation of polar compounds in the oil. Presently, the rate of cooking oil degradation is indicated by the percentages of its total polar compounds (TPC). In this study, impedance sensor probe was designed to assess the cooking oil degradation at several heating time intervals by measuring the changes on its electrical impedance. The probe was designed using interdigitated electrodes (IDEs) platform. In total of 30 samples of 130 ml palm oil were heated at 180o C up to 30 hours using a laboratory oven. For each one hour increment, one sample was taken out of the oven and cooled at room temperature before measuring the impedance value using the designed probe which connected to a LCR meter. The TPC of the oil samples was measured using Testo 270 cooking oil tester (InstruMartInc, Germany). The discrimination between the electrical impedance values at different heating hours of oil samples was analyzed and correlated to their TPC measurements. Preliminary results showed good correlation between the oil electrical impedance with their TPC value. The designed sensor probe has good potential for simple and inexpensive way of monitoring cooking oil degradation.